Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s12544-017-0278-0
|View full text |Cite
|
Sign up to set email alerts
|

Restrained mobility in a high-accessible and migrant-rich area in downtown Beijing

Abstract: Purpose Immigrant travel has become an emerging research field in transportation planning. A handful of scholars have studied the travel behavior of residents in immigrant enclaves in North America. However, thus far, there has been no analysis of the travel behavior of residents living in migrant-rich neighborhoods in China. Additionally, previous studies rarely explored whether these (im)migrants could benefit from resources outside the neighborhoods, and the determinants of their travel to destinations outs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…They need immigrants to be mobile and able to move around to improve the integration process. Again, research is confirmed [2,3].…”
Section: Interpretation and Recommendationsmentioning
confidence: 78%
See 3 more Smart Citations
“…They need immigrants to be mobile and able to move around to improve the integration process. Again, research is confirmed [2,3].…”
Section: Interpretation and Recommendationsmentioning
confidence: 78%
“…In general, research agrees that a lack of mobility leads to enclaves, social exclusion, and reduced job opportunities. A negative impact on the integration of the immigrants is predicted [2,19].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This is particularly true for large cities where human activities are highly concentrated with limited resources [2,3]. It is found that excessive human activities have not only led to serious environmental problems such as air pollution and degradation of ecosystem services [4,5], but have also caused many other social and economic problems, including occupational and residential segregations, increased inequality, and impairment of spatial fairness [6,7]. It is no wonder that the impact of human activities on both the natural and built environments has been extensively examined in the literature, wherein the concept of human activity intensity (HAI) has been proposed as a measure of the extent by which land surface has been affected by human activities.…”
Section: Introductionmentioning
confidence: 99%